(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The export of labour in the Philippines has been a state response to a failing economy. Filipino labour, one of the biggest assets of the Philippine state, became in great demand in the United States, Middle East, Europe and the rich countries of Asia. In the last decades, the demand for female labour has equalled and sometimes surpassed that for male labour. Female foreign workers from the Philippines laboured mostly as maids, caregivers, medical personnel and entertainers. My study posits the idea that the social conditioning of the Filipina in the home and the community prepares her to be a good Filipino woman and that these same traits make her an attractive commodity in the global market. Local and global expectations split the Filipina worker's subjectivity. For instance, trained to be an agent of nurture within the family, she is preferred by employers in nursing and caregiving facilities overseas. Trained in the musical culture of the Filipino household and community, she is preferred as an entertainer in hotels and bars. The study furthermore examines the tension between the cultivation of a local cultural good and its transformation into an instrument of commercial profit and exploitation when it enters the globalised space. The globalised subjectivity returns to the local with mixed results. This paper will use literary texts on the overseas Filipina worker as they explore her evolving subjectivity during the process of glocalisation.